The Function and Therapeutic Potential of Long Non-coding RNAs in Cardiovascular Development and Disease - Clarissa P.C. Gomes; Helen Spencer; Kerrie L. Ford; Lauriane Y.M. Michel; Andrew H. Baker; Costanza Emanueli; Jean-Luc Balligand; Yvan Devaux (Elsevier, 2017)
The popularization of genome-wide analyses and RNA sequencing led to the discovery that a large part of the human genome, while effectively transcribed, does not encode proteins. Long non-coding RNAs have emerged as critical regulators of gene expression in both normal and disease states. Studies of long non-coding RNAs expressed in the heart, in combination with gene association studies, revealed that these molecules are regulated during cardiovascular development and disease. Some long non-coding RNAs have been functionally implicated in cardiac pathophysiology and constitute potential therapeutic targets. Here, we review the current knowledge of the function of long non-coding RNAs in the cardiovascular system, with an emphasis on cardiovascular development and biology, focusing on hypertension, coronary artery disease, myocardial infarction, ischemia, and heart failure. We discuss potential therapeutic implications and the challenges of long non-coding RNA research, with directions for future research and translational focus. Keywords: transcriptomics, RNAs, long non-coding RNAs, cardiovascular system, cardiovascular development, cardiovascular disease, vascular disease, therapy, non-coding RNAs